Lymphoscintigraphy in breast cancer: a short review about the impact on upper limb after surgical treatment - Bergmann,Anke (2008)
Breast cancer is still associated with high mortality rates and one of the most important factors governing long survival is accurate and early diagnosis. In underdeveloped countries, this disease frequently is only detected in advanced stages; however, through mammography, many women have been diagnosed at early stages. In this context, the sentinel lymph node (SLN) technique is associated with less postoperative morbidity compared to axillary lymphadenectomy. Lymphoscintigraphy has emerged as a method for the evaluation of lymphatic drainage chains in various tumours, being both accurate and non invasive. The aim of this work is to present the main aspects which cause controversy about SLN and lymphoscintigraphy and the impact that these procedures have had on lymphedema after surgical treatment for breast cancer. A short review including papers in English, Spanish and Portuguese, available on Lilacs and Medline database, published between January, 2000 and July, 2008 was performed. The key words breast cancer, lymphoscintigraphy, SLN biopsy, lymphedema were used. Various studies have aimed to compare the incidence and prevalence of lymphedema according to the technique used; however, the population subjected to SLN is different from the one with indication for axillary lymphadenectomy regarding staging. Moreover, little is known about long term morbidity since it is a relatively new technique. In conclusion, the development of surgical techniques has permitted to minimize deformities and the current trend is that these techniques be as conservative as possible. Thus, lymphoscintigraphy plays an important role in the identification of SLN, contributing to the prevention and minimization of postoperative complications.